Experimental investigation of the effects of the turbulence on the impact force of flash flood - Gu, Haihua; Lei, Yu (Frontiers in Earth Science, 2023)
Flash floods cause damage to engineering structures and buildings mainly due to their huge impact force. Scientific investigation of the impact process of flash floods has significant theoretical and engineering implications in ensuring the safety of flood-resistant structures and human life. In this experimental study, the impact pressure and flow velocity in the flow field were measured synchronously using the impact detection system and a particle image velocimetry system in a water channel and the effects of the turbulence structure on the impact process of flash flood were investigated. As shown by the experimental measurements, the large-scale coherent structure in the flow field reached six times the boundary layer thickness. The turbulence and impact force energy spectra were very similar in the low-frequency, large-scale wave band, indicating that the large-scale turbulence structure dominated the impact process. Both the mean and maximum impact pressures increased with the turbulence kinetic energy. An equation for impact force characterization that considers the effects of turbulence and thus was more accurate was given, providing a theoretical basis for the protection of engineering structures from the damage by flash floods.